The Role of UbD in Developing Students’ Mathematical Problem-Solving Skills: A Literature Review - Fatqurhohman Fatqurhohman; Tatik Retno Murniasih; Rahmad Bustanul Anwar; Fahmi Abdul Halim (Review of Education, Science, and Technology, 2025)
21st century learning demands strategies that go beyond the mere transfer of knowledge, emphasizing instead the development of higher-order thinking skills. Understanding by Design (UbD) emerges as a relevant approach as it highlights backward design through the formulation of end goals, authentic assessment, and meaningful learning experiences. This study aims to analyze the contribution of UbD to problem-solving skills through a systematic literature review. Out of 50 articles reviewed, six met the criteria of relevance and methodological quality using the Quality Assessment instruments (QA1, QA2, QA3). The findings indicate that UbD enhances conceptual understanding, motivation, and learners’ ability to connect abstract concepts with real-life contexts and to transfer knowledge to new situations. Nevertheless, teachers’ readiness to design instruction consistent with UbD principles remains a major challenge. The implications of this study affirm that UbD holds strong potential as an adaptive instructional design framework aligned with the demands of 21st century curricula. Future research is recommended to examine the longitudinal implementation of UbD at the secondary level with a focus on strengthening critical thinking and mathematical problem-solving skills.